2019
DOI: 10.3390/f10111032
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Drought and Salinity on Sweetgum Tree (Liquidambar styraciflua L.): Understanding Tree Ecophysiological Responses in the Urban Context

Abstract: Understanding urban tree responses to drought, salt stress, and co-occurring stresses, as well as the capability to recover afterward, is important to prevent the cited stresses’ negative effects on tree performance and ecological functionality. We investigated the impact of drought and salinity, alone and in combination, on leaf water potential, gas exchange, chlorophyll a fluorescence, xanthophyll cycle pigments, and isoprene emission of the urban tree species Liquidambar styraciflua L. Generally, drought ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Indeed, the osmotic stress induced by salinity, which can lead to a reduction of CO2 assimilation by the plant and consequently an inhibition of photosynthesis (Ezquer et al 2020;Yang et al, 2020). In addition, salinity is a constraint that disrupt photochemical reactions of photosynthesis, especially at the PSII level (Baraldi et al 2019;Zahra et al, 2022). This study also showed that the decrease in stomatal conductance was related to a reduction in chlorophyll fluorescence (Fv/Fm) in plants subjected to salt stress.…”
Section: Discussionmentioning
confidence: 53%
“…Indeed, the osmotic stress induced by salinity, which can lead to a reduction of CO2 assimilation by the plant and consequently an inhibition of photosynthesis (Ezquer et al 2020;Yang et al, 2020). In addition, salinity is a constraint that disrupt photochemical reactions of photosynthesis, especially at the PSII level (Baraldi et al 2019;Zahra et al, 2022). This study also showed that the decrease in stomatal conductance was related to a reduction in chlorophyll fluorescence (Fv/Fm) in plants subjected to salt stress.…”
Section: Discussionmentioning
confidence: 53%
“…Resistance can include avoidance, tolerance and a combination of these two methods of defense against the stress factor (Blomqvist 1998). The following methods can be used to relieve salt stress by trees: inhibition of Cl and Na uptake and redistribution of elements from leaves to other parts of plants (Shelkeet al 2019), the storage of Na + and Cl − in cell structures (Baetz et al 2016), the induction of antioxidant enzymes and hormones (Zhao et al 2019;Sarker and Oba 2020), the presence of ectomycorrhizal fungi (Zwiazek et al 2019;Olchowik et al 2021), the accumulation of compatible compounds, the increased conversion of xanthophyll pigments (Baraldi et al 2019), and the presence of genes that can increase salt tolerance (Parihar et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Salt tolerance of annual crops can be assessed by comparing biomass production by the plant growing in saline conditions to that when grown in control conditions over a certain time. However, for woody plants, usually with a relatively slower growth rate, other ways than biomass comparison, e.g., simple and quick physiological variables may be employed to compare salt tolerance (Baraldi et al 2019).…”
Section: Introductionmentioning
confidence: 99%